The atomic decomposition of harmonic functions satisfying certain conditions of integrability - Krzysztof Bogdan (International Journal of Mathematics and Mathematical Sciences, 1995)
Distributions on Euclidean spaces with derivatives of their Poisson integral satisfying certain natural conditions of integrability are represented as sums of weighted atoms. The atomic decomposition is obtained by means of the Calderón reproducing formula.